Microcephalic osteodysplastic primordial dwarfism type II: Additional nine patients with implications on phenotype and genotype correlation. Issue 6 (8th April 2020) - Abdel‐Salam, Ghada M. H.; Sayed, Inas S. M.; Afifi, Hanan H.; Abdel‐Ghafar, Sherif F.; Abouzaid, Maha R.; Ismail, Samira I.; Aglan, Mona S.; Issa, Mahmoud Y.; EL‐Bassyouni, Hala T.; El‐Kamah, Ghada; Effat, Laila K.; Eid, Maha; et al.
Abstract: PCNT encodes a large coiled‐ protein localizing to pericentriolar material and is associated with microcephalic osteodysplastic primordial dwarfism type II syndrome (MOPD II). We report our experience of nine new patients from seven unrelated consanguineous Egyptian families with the distinctive clinical features of MOPD II in whom a customized NGS panel showed homozygous truncating variants of PCNT . The NGS panel results were validated thereafter using Sanger sequencing revealing three previously reported and three novel PCNT pathogenic variants. The core phenotype appeared homogeneous to what had been reported before although patients differed in the severity showing inter and intra familial variability. The orodental pattern showed atrophic alveolar ridge (five patients), rootless tooth (four patients), tooth agenesis (three patients), and malformed tooth (three patients). In addition, mesiodens was a novel finding found in one patient. The novel c.9394‐1G>T variant was found in two sibs who had tooth agenesis. CNS anomalies with possible vascular sequelae were documented in two male patients (22.2%). Simplified gyral pattern with poor development of the frontal horns of lateral ventricles was seen in four patients and mild thinning of the corpus callosum in two patients. Unilateral coronal craniosynstosis was noted in one patient and thick but short corpus callosum was an unusual finding noted in another. The later has not been reported before. Our results refine the clinical, neuroradiological, and orodental features and expand the molecular spectrum of MOPD II.